MATRA HELPS PRODUCE TALENTED, SKILLED AND COMPETENT FUTURE ARCHITECTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, August 2016 – Over 600 students from 21 institutions of higher learning, including two from abroad, namely Universiti Shiah Kuala, Indonesia and Omdurman Islamic University, Sudan gathered in Universiti Sains Malaysia (USM) from 17 to 21 August 2016 to participate in the 28 Architectural Students Workshop (MATRA 2016).